A critical review of urological practice during the coronavirus disease 2019 pandemic and the emerging role of telemedicine. (May 2021) - Fonseka, T; Ellis, R; Salem, HA
The recent coronavirus disease 2019 outbreak was met by major reconfiguration of Urology health care services with cancellation of elective surgery and deployment of non face to face models for providing outpatient care. Urologists were faced with challenging decisions to stratify their patients into risk groups for assigning the appropriate, safe method of care delivery. Guidelines were swiftly produced by Urological societies to enhance this process but there has been limited uniformity and multiple publications from several institutions. We have conducted this critical review to appraise the current recommendations for providing Urology care during the coronavirus disease 2019 pandemic. The secondary outcome was identifying novel models for care delivery. Results were presented in tables categorising the recommendation by disease and its risk stratification. Results were presented according to the aspect of care: triage for surgery, operative, post-operative and outpatient care. This review reported differing recommendations from Urological societies on the prioritisation of services with limited consideration for individual patient-related factors. Telemedicine has been utilised well during the pandemic to maintain patient pathways. The role of telemedicine in future Urological practice looks promising and more development is required. Level of evidence: Not applicable.